Exercising associational and networked power through the use of digital technology by workers in global value chains - Nicole Helmerich; Gale Raj-Reichert; Sabrina Zajak (Competition & Change, 2021)
While there are heated debates about how digitalization affects production, management and consumption in the context of global value chains, less attention is paid to how workers use digital technologies to organize and formulate demands and hence exercise power. This paper explores how workers in supplier factories in global value chains use different digital tools to exercise and enhance their power resources to improve working conditions. Combining the global value chain framework and concepts from labour sociology on worker power, the paper uses examples from the garment industry in Honduras and the footwear industry in China to show how workers used old and new digital tools to create and enhance associational and networked powers. Digital tools were used by workers and their allies in the global value chain to lower costs of communication, increase information exchange and participate in transnational campaigns during labour struggles vis-à-vis firms and governments in structurally and politically repressive environments. The paper contributes to our understanding of how workers use of digital technologies to exercise and combine different resources of power in online and offline actions in global value chains, as well as how they are confronted by new dimensions of constrains which include digital surveillance and control by the state.
Keywords: 330; worker power; digitalization; associational power; networked power; global value chains